Influence of cooking on the levels of bioactive compounds in Purple Majesty potato observed via chemical and spectroscopic means. (15th April 2015) - Lemos, M. Adília; Aliyu, Maryam M.; Hungerford, Graham
Highlights: Purple Majesty potato is a rich source of polyphenolic compounds, including anthocyanins. Anthocyanin levels increased using different cooking techniques (except baking). All cooking methods had a detrimental effect on the levels of total phenolics. Overall the anti-oxidant activity was not affected. Time-resolved fluorescence promising in assessing bioactive content. Abstract: Tubers rich in phytochemicals can exhibit a potential health benefit. This work aims at studying the relative effect of different domestic cooking techniques by monitoring the level of total phenolic compounds (TP), total anthocyanins (TA) and anti-oxidant activity (AOA) on a variety of pigmented potatoes. Raw purple potatoes are a good source of anthocyanins (219 mg/kg FW) and the level of these compounds increased using different cooking techniques, with the exception of baking. However, the levels of phenolic compounds (originally 209 mg GAE/100 g FW) decreased in the cooked potatoes. Although potatoes contain different antioxidants in this work the antioxidant activity seems to be related to the levels of phenolic compounds present in the pigmented potato. The fact that some of the compounds present fluoresce enabled both steady state and time-resolved fluorescence techniques to be assessed as a non destructive means of monitoring. This elucidated the presence of different components ( via spectral deconvolution and time-resolved emission spectra). Their relative contribution to the fluorescence emission was found to be affected by the different cooking process, with a longer wavelength emission appearing to relate to reflect the presence of anthocyanins.